2016
DOI: 10.1038/pr.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil improves monocrotaline-induced pulmonary hypertension rat model

Abstract: Background: Pulmonary arterial hypertension (PAH) progressively leads to increases in pulmonary vasoconstriction. Modafinil plays a role in vasorelaxation and blocking KCa3.1 channel with a result of elevating intracellular cyclic adenosine monophosphate (cAMP) levels. The purpose of this study is to evaluate the effects on modafinil in monocrotaline (MCT)-induced PAH rat. Methods: The rats were separated into three groups: the control group, the monocrotaline (M) group (MCT 60 mg/kg), and the modafinil (MD) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In the present and previous studies, ET-1 and ERA protein expression levels were increased at weeks 2 and 4 after MCT injection, suggesting their importance in the progression of cardiopulmonary pathology in MCT-induced PAH rat model 14). In the 2016 study by Lee et al15), plasma ET-1 levels were found to be significantly increased in the MCT model 16). The protein expression level of eNOS decreased from 1 week after the MCT injection, whereas the NOX4 protein level was increased at week 4 in lung tissues of the MCT treated rat model.…”
Section: Discussionsupporting
confidence: 65%
“…In the present and previous studies, ET-1 and ERA protein expression levels were increased at weeks 2 and 4 after MCT injection, suggesting their importance in the progression of cardiopulmonary pathology in MCT-induced PAH rat model 14). In the 2016 study by Lee et al15), plasma ET-1 levels were found to be significantly increased in the MCT model 16). The protein expression level of eNOS decreased from 1 week after the MCT injection, whereas the NOX4 protein level was increased at week 4 in lung tissues of the MCT treated rat model.…”
Section: Discussionsupporting
confidence: 65%
“…Primary cultures of PASMCs were isolated from 10-week-old rats as previously described [ 15 ]. Briefly, a segment of the main pulmonary artery was excised and placed in Dulbecco’s modified Eagle medium containing 10% fetal bovine serum, 1% penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…However, elevated ET-1 levels can activate vascular smooth muscle cells, inducing proliferation, hypertrophy, and synthesis of extracellular matrix, which lead to a diverse range of cardiovascular diseases including atherosclerosis, cardiac hypertrophy and pulmonary hypertension[8, 9]. The detrimental effects exerted by ET-1 on the vasculature include excessive accumulation of reactive oxygen species[10], promotion of vascular smooth muscle cells proliferation[11], and chronic vascular inflammation[12]. …”
Section: Introductionmentioning
confidence: 99%